Composite Materials Engineering, Volume 1 Fundamentals of Composite Materials (Springer Singapore, 2018)
This book is the first of two volumes providing comprehensive coverage of the fundamental knowledge and technology of composite materials. It covers a variety of design, fabrication and characterization methods as applied to composite materials, particularly focusing on the fiber-reinforcement mechanism and related examples. It is ideal for graduate students, researchers, and professionals in the fields of Materials Science and Engineering, and Mechanical Engineering.